Development of Pop Up Book Media Based on an Investigative Approach to Improve The Matematical Communication Skill of Junior High School Students - Kariadinata, Rahayu; Ajahra, Euis Sinta; Jihad, Asep (Jurnal Analisa, 2024)
Siswa SMP sering mengalami kesulitan dalam memahami konsep matematika yang abstrak dan membutuhkan bantuan visual dalam proses pembelajaran. Pengembangan media buku pop-up berbasis pendekatan investigasi bertujuan memberikan representasi visual dari konsep matematika. Penelitian ini bertujuan menilai validitas, praktikabilitas, dan efektivitas media buku pop-up berbasis pendekatan investigasi serta mengukur peningkatan kemampuan komunikasi matematis siswa sebelum dan setelah menggunakan buku pop-up. Metode penelitian yang digunakan adalah Penelitian dan Pengembangan (R&D) dengan menggunakan model 4D (define, design, develop, and disseminate). Hasil penelitian menunjukkan bahwa media ini sangat valid dari segi media dan materi. Praktikabilitas media ini dinilai sangat praktis, dan efektivitasnya diklasifikasikan sebagai sangat tinggi. Terdapat peningkatan yang signifikan dalam kemampuan komunikasi matematis siswa, yang dikategorikan sebagai tinggi.Â Junior high school students often struggle with grasping abstract mathematical concepts and benefit from visual aids in their learning process. The development of investigative-based pop-up book media aims to provide visual representations of these concepts. This research aims to assess the validity, practicality, and effectiveness of the investigative-based pop-up book media and to measure the improvement in students' mathematical communication skills before and after using the pop-up book. The research methodology employed is Research and Development (R&D) using the 4D model (define, design, develop, and disseminate). The results indicate that the media is highly valid in terms of both media and content aspects. Its practicality is rated as highly practical, and its effectiveness is classified as very high. There is a significant improvement in the mathematical communication skills of junior high school students, categorized as high.